PENGARUH EFEK IKLAN ENDORSEMENT TERHADAP NIAT KONSUMEN UNTUK BERBELANJA ONLINE DI KOTA BATAM - Hasan, Golan (Journal of Accounting and Management Innovation, 2020)
The purpose of this research was to find out and study the online buying behavior influenced by advertising or endorsement of celebrities in social media trading. Online purchase intentions were in Batam influenced by celebrity endorsement advertisements using variable trust in online shopping, convenience of online shopping, customer services offered by online shopping and subjective norm as independent variables, attitude towards online shopping as intervening variables, intention to shop online as dependent variable.There were 400 sample respondents used in this study obtained from students and residents in Batam using the selection of purposive sampling method and the data collected is processed using a partial least square (PLS) program.The results of this study explain that online shopping intentions are influenced by endorsement advertising through social media, the variable trust in online shopping has significant effect on intention to shop online. Trust in online shopping has a significant effect on attitude towards online. Convenience of online shopping has a significant effect on attitude towards online. The dependent variable intention to shop online and convenience of online shopping have significant effect on intention to shop online. Customer services of offered by online shopping has significant effect on intention to shop online. Customer services of offered online shopping have significant effect on attitude towards online. Independent variable intention to shop online, attitude towards online shopping have no significant effect on intention to shop online and lastly subjective norm has no effect on intention to shop online.Keywords:Endorsement, Intention To Shop Online